A metal-free transformation of alkynes to carbonyls directed by remote OH group. Issue 15 (27th June 2016) - Chen, Dao-Qian; Guo, Chun-Huan; Zhang, Heng-Rui; Jin, Dong-Po; Li, Xue-Song; Gao, Pin; Wu, Xin-Xing; Liu, Xue-Yuan; Liang, Yong-Min
Abstract : A remote OH group-directed metal-free transformation of alkynes to carbonyl compounds has been developed. Abstract : A remote OH group-directed metal-free transformation of alkynes to carbonyl compounds has been developed. Using only HOAc and EtOH solvent, this reaction elegantly converts alkynes into valuable ketones by remote hydroxyl group activation. Through comparison and isotope labeling experiments, it was confirmed that the process operates via a hydration reaction involving an acetic acid molecule, instead of a water molecule.